PEMEROLEHAN BAHASA INDONESIA SEBAGAI B2 (BAHASA KEDUA) PADA ANAK DOWN SYNDROME DI LKS DARUL AZHAR - Erma Lestari; Cattleya Wahyu Pravitha; Muhammad Yusi Kamhar (Inteligensi : Jurnal Ilmu Pendidikan, 2022)
This study aims to determine the acquisition of Indonesian as a second language in children with Down syndrome. This research is important to be improved in order to improve the ability to speak Indonesian because it is the language of unity in Indonesian society. The research used qualitative method with samples obtained from 20 children with special needs at the LKS Darul Azhar orphanage through interviews and dialogue with children with special needs at the LKS Darul Azhar orphanage. These children are Down syndrome children who are introduced to Indonesian as B2 or a second language to learn, although not as fast as ordinary children. Environmental support and teaching methods for acquiring a second language greatly affect the tempo of acquiring B2. The acquisition of a second language (Indonesian) in Down Syndrome children needs to be developed because it has a positive impact on the development of communication which is also supported by the process of acquiring learning through training in vowel errors, preliminary tests through pronunciation of words and expressions, finding and characterizing lexical and grammatical.